PENGEMBANGAN PELAKSANAAN PEMBELAJARAN MENULIS TEKS EKSPOSISI MENGGUNAKAN MODEL SUGESTI IMAJINASI DENGAN AUDIO VISUAL SISWA KELAS X SMK NEGERI 15 SAMARINDA - Yuli Agustina (LOA: Jurnal Ketatabahasaan dan Kesusastraan, 2019)
It studies about the improvement of exposition text writing. It uses imagination suggestion model of audio visual aided instruction. It aims to develop a product in the form of the learning implementation of exposition text writing on 10th Grade of SMK Negeri 15 Samarinda. It applies research and development method. Two supervisors evaluate the lesson plan (RPP) and its mean score is 78% which is in a good category. On the implementation, its mean score is 86,69%, good category. The data are collected from questionnaires and assignments. The development of the learning implementation reveals: (1) the feasibility of the development design; (2) the learning implementation feasibility of exposition text writing done by the teacher. In a small group examination, both materials and presentations do not reach the Minimum Criteria of Mastery Learning (KKM) 75; and 3) the learning effectiveness. It is indicated by the result of the writing that reaches ≤ 75, the result of the study that reaches KKM with 100% mastery percentage and mean score of 79,26.